2021
DOI: 10.1002/bit.27743
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized poly(vinylalcohol) and poly(vinylpyrrolidone) based patches with tunable mechanical properties for cardiac tissue engineering applications

Abstract: Polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) are the two most investigated biopolymers for various tissue engineering applications. However, their poor tensile strength renders them unsuitable for cardiac tissue engineering (CTE).In this study, we developed and evaluated PVA-PVP-based patches, plasticized with glycerol or propylene glycol (0.1%-0.4%; v:v), for their application in CTE. The cardiac patches were evaluated for their physico-chemical (weight, thickness, folding endurance, FT-IR, and swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…However, sharper creases can be observed in the images of formulations F4 and F6 (Figure 4d,f, respectively). The creases could be explained by the different stiffness of triple-helix gelatin molecules compared to PVP or PVA molecules [64,65]. The presence of the undissolved drug was not observed, as can be seen in Figure 4b,d,f [66].…”
Section: Field Emission Scanning Electron Microscope (Fesem)mentioning
confidence: 86%
“…However, sharper creases can be observed in the images of formulations F4 and F6 (Figure 4d,f, respectively). The creases could be explained by the different stiffness of triple-helix gelatin molecules compared to PVP or PVA molecules [64,65]. The presence of the undissolved drug was not observed, as can be seen in Figure 4b,d,f [66].…”
Section: Field Emission Scanning Electron Microscope (Fesem)mentioning
confidence: 86%
“…Although the perfusable vascular analogs have exhibited promising results towards the construction of various organs in vitro , the utilization of such biomimetic constructs in tissue regeneration upon clinical transplantation place high demands on the vascular alignment, which still remains limited for regeneration and implantation of large-scale engineered tissues, such as skeletal muscle, shin epithelium, liver, and other major organs [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ]. Indeed, capillaries are the places where blood and tissues exchange substances, including nutrition and waste products [ 62 , 63 ].…”
Section: Regeneration Mechanism Of Vascular Networkmentioning
confidence: 99%
“…An impressive spectrum of cell biology, versatile hydrogels, and clinical pathology has enabled the formation of 3D tissue analogs with promoted vascularization. To date, an extensive study has demonstrated various organ types that can be mimicked by hydrogels, including but not limited to bone [ 77 , 95 , [163] , [164] , [165] ], kidney [ [52] , [53] , [54] ], liver [ [55] , [56] , [57] ], lung [ 160 , 166 , 167 ], muscle [ [58] , [59] , [60] , [61] ], and brain [ 138 , 168 ]. Ultimately, the generation of these reproducible and accurate 3D organoids has extended the downstream translational applications, including tissue regeneration ( Table 3 ), organ-on-chips ( Table 4 ), and drug screening ( Table 5 ).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…In addition, synthetic materials can be engineered with biological cues to interact with the physiological microenvironment. 41) Over the past decade, materials such as poly(Īµ-caprolactone) (PCL), 37) 42) poly(glycerol sebacate) (PGS), 43) 44) poly(lactic-co-glycolic acid) (PLGA), 45) biodegradable polyurethane (PU), 46) poly(l-lactide) (PLLA), 47) 48) poly(vinyl alcohol), 49) and polyethylene glycol(+) 24) 35) 36) 50) 51) have been commonly used for the engineering of cardiac patches. However, whether synthetic materials can fully mimic physiological conditions of the ECM remain questionable, as their structural composition drastically differs from their biological counterparts.…”
Section: Engineered Tissue Patch Constructs For Cardiac Regenerationmentioning
confidence: 99%
“…Though there remain shortcomings and challenges, the promising results of numerous clinical trials demonstrate the potential of biomaterials for clinical applications regarding cardiac regeneration ( Table 2 ). 4) 8) 10) 11) 13) 14) 18) 19) 20) 21) 23) 24) 25) 34) 35) 36) 37) 42) 43) 44) 45) 46) 47) 48) 49) 50) 51) 52) 56) 65) 77) 82) 87) 91) 98) 99) With the advent of stem cell-based and genome editing technologies for cardiac engineering, the translational potential of these biomaterials-based approaches will continue to grow. 100) …”
Section: Conclusion and Future Perspectiveunclassified